Historical and cultural stages of development of Kabardino-Circassian children's literature - Khamisha T. Timizhev; Naima B. Bozieva (Кавказология, 2023)
This article examines the historical and cultural stages of the development of Kabardino-Circassian children’s literature. The main attention is paid to the inseparable connection of education and upbringing of children. The work focuses on the fact that children’s literature is a part of fiction, with its own characteristics arising from its educational and academic tasks: it enriches young readers’ understanding of the past and present of their people, helps to assimilate high moral principles, reveals the beauty of a man’s feat in the name of the Motherland. The study of the evolutionary development of children’s literature is dictated by the requirements of deep scientific coverage of literary process and tasks of further development of national literature. The relevance of the research is determined by the insufficient study of children’s literature, the need to fill the existing gap in modern Adyghe literary studies. This article also defines the term “children’s literature”, provides views of Russian and foreign scientists, examines the first works in the Adyghe language of Circassian educators. During the study, a set of scientific methods was applied, including comparative-historical, description, literary analysis. The results obtained can be used in further research of the history of Adyghe (Kabardino-Circassian) children’s literature, as well as the development of special courses and research in the field of national philology.